Media dalam Pendidikan Islam - Darwis, Muhajir; Ramadhanisa, Afifah; Nurrita, Nurrita; Nisak, Hidayatun; Otapiyarahmadona, Selfi; Azura, Zaskya (Al-Aulia: Jurnal Pendidikan dan Ilmu-Ilmu Keislaman, 2025)
The development of information and communication technology has brought significant transformations in various fields, including Islamic education. However, many Islamic educational institutions still rely on conventional media such as blackboards, resulting in a gap between the potential of technology and its use in learning. This study aims to analyze the role and types of media in Islamic education, identify obstacles to its implementation, and formulate strategies for effective media utilization based on Islamic values. A qualitative method with a library research approach was applied, collecting data from literature. The results show that conventional and digital media are effective in conveying Islamic values, but are hampered by low teacher digital literacy, limited infrastructure, and lack of regulation. Strategies such as teacher training, development of local culture-based media, and integration of Islamic values ​​in digital content are needed to create adaptive learning. This study provides a basis for the development of relevant Islamic education in the digital era.